Pengaruh Lifestyle Flash Sale Promotion dan Diskon Terhadap Minat Beli Pengguna Shopee (Study Kasus pada Gen Z Pengguna Shopee) - Sinaga, Rojali A.; Tarigan, Feriani Astuti; Siregar, August Halomoan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This research is motivated by the increasing number of Shopee users. This study aims to determine the influence of Lifestyle, Flash Sale Promotion, and Discount on Purchase Intention of Shopee application users in Gen Z situations. This study uses a survey method with a sampling technique using the Lemeshow approach with a maximum estimate of 50% and an error rate of 10%. The sample size in this study consists of 100 samples. Data were analyzed using linear regression analysis. To assess the validity and reliability of the test, 30 consumers were selected from the entire population considered. This study uses a quantitative method. The research method used in this study is quantitative descriptive research, which aims to thoroughly analyze the subject matter. The results show that lifestyle, Lifestyle, Flash Sale Promotion, and Discount have a positive and significant effect on Purchase Intention of Shopee users in Gen Z. The coefficient of determination of 0.236 or 23.6% indicates that the combined influence of lifestyle, Flash Sale Promotion, and Discount in explaining consumer usage decisions is 23.6%. The remaining 76.4% of the variance is likely due to factors outside the studied variables, such as service quality, shipping costs, and so on. The results of this study can be used as a reference for Shopee app developers to improve service quality and increase user trust.